Penguatan Karakter Peserta Didik dalam Pembelajaran Proyek Penguatan Profil Pelajar Pancasila - Dinda Olivia; Gina Hasyfia Nabila; Indah Juliana (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The Learning Project for Strengthening the Pancasila Student Profile (P5) is one of the learning innovations developed by the Ministry of Education and Culture (Kemendikbud) to strengthen the character of students in accordance with Pancasila values. P5 learning is carried out across subjects and involves students in various project activities that are meaningful and have a real impact on the surrounding environment. Through P5 learning, students are expected to be able to develop various basic competencies, such as critical thinking, creative, communicative and collaborative. Apart from that, students are also expected to be able to practice Pancasila values ​​in their daily lives.